Bacterial, Fungal, Parasitic, and Viral Myositis - Crum-Cianflone, Nancy F. (American Society for Microbiology (ASM), 2008)
Infectious myositis may be caused by a broad range of bacterial, fungal, parasitic, and viral agents. Infectious myositis is overall uncommon given the relative resistance of the musculature to infection. For example, inciting events, including trauma, surgery, or the presence of foreign bodies or devitalized tissue, are often present in cases of bacterial myositis. Bacterial causes are categorized by clinical presentation, anatomic location, and causative organisms into the categories of pyomyositis, psoas abscess, Staphylococcus aureus myositis, group A streptococcal necrotizing myositis, group B streptococcal myositis, clostridial gas gangrene, and nonclostridial myositis. Fungal myositis is rare and usually occurs among immunocompromised hosts. Parasitic myositis is most commonly a result of trichinosis or cystericercosis, but other protozoa or helminths may be involved. A parasitic cause of myositis is suggested by the travel history and presence of eosinophilia. Viruses may cause diffuse muscle involvement with clinical manifestations, such as benign acute myositis (most commonly due to influenza virus), pleurodynia (coxsackievirus B), acute rhabdomyolysis, or an immune-mediated polymyositis. The diagnosis of myositis is suggested by the clinical picture and radiologic imaging, and the etiologic agent is confirmed by microbiologic or serologic testing. Therapy is based on the clinical presentation and the underlying pathogen.